PERANAN KUALITAS PRODUK DALAM KEPUTUSAN PEMBELIAN SMARTPHONE SAMSUNG ANDROID (Studi Kasus Pada Mahasiswa STIE Nasional Banjarmasin Angkatan 2014) - Rizki Amalia Afriana; Saidah - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2016)
Abstract, Problems examined regarding the role of the variable product quality (performance, reliability, features, durability, suitability, design) in the purchase decision Smartphone Samsung. The study population was a student STIE Nasional 2014 Banjarmasin generation Samsung Android smartphone users as many as 107 users and samples taken as many as 30 respondents. The method used in this research is descriptive method. Results of this study is that the variable performance indicators operating system owned by Samsung Smartphone Android already is the latest version, the variable Reliability the machine is not easy to heat, variable features with the camera quality is good, the variable resistance with indicator resilience LCD durable, variable compliance with suitability indicators according to the desired shape young people today and the variable design with an attractive design indicators were appropriate.